1997
DOI: 10.1145/256303.256311
|View full text |Cite
|
Sign up to set email alerts
|

On the completeness of object-creating database transformation languages

Abstract: Object-oriented applications of database systems require database transformations involving nonstandard functionalities such as set manipulation and object creation, that is, the introduction of new domain elements. To deal with these functionalities, Abiteboul and Kanellakis [1989] introduced the "determinate" transformations as a generalization of the standard domain-preserving transformations. The obvious extensions of complete standard database programming languages, however, are not complete for the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 22 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…One can extend the notion of generic query and update, however, to allow for value invention: the introduction of new data elements in the result [5,3,31,2].…”
Section: Value Inventionmentioning
confidence: 99%
“…One can extend the notion of generic query and update, however, to allow for value invention: the introduction of new data elements in the result [5,3,31,2].…”
Section: Value Inventionmentioning
confidence: 99%
“…We collaborated on that question and that led to our joint paper (with Andreas Blass) on ASMs and computationally complete query languages [6,7]. In short, it turns out that choiceless polynomial time is the same as the polynomial-time fragment of a natural complete query language based on first-order logic, object creation [10], and iteration. We also showed that the "non-flat" character of choiceless polynomial time, be it through arbitrarily deeply nested sets, or through object creation, is essential to its high expressive power.…”
Section: Choiceless Polynomial Timementioning
confidence: 99%
“…However, motivated by recent applications of databases in object-oriented environments, the theory of database queries has recently been extended beyond domain-preserving functions, allowing for the introduction of new domain elements in the result of a query [1], [16]. This extended theory, needed to account for the creation of new objects in an object-oriented database, is fully applicable to the particular case of graphs.…”
Section: Generic Completenessmentioning
confidence: 99%
“…A powerful language for expressing object-creating queries is the language provided by the GOOD model, a graph-oriented model for object databases [11]. It has been shown that the GOOD language is computationally complete in that the language can express precisely all constructive computable generic graph functions [15], [16].…”
Section: Generic Completenessmentioning
confidence: 99%
See 1 more Smart Citation